South American Balanced Canoes: Stages in the Invention of the Double Outrigger (2022)
eng: During the St. George Epedition to the Pacific en 1924, whilst the ship lay off the island of Gorgona, situated some 20 miles distant from the Pacific coast of Colombia (S.A.), canoes sailed over from the mainland almost daily; the majority came for fishing, some to attend to a granzing property under development at the south end of the island, whilst two brought Customs officers to learn what business a strange ship had at this lonely island.